Non-monotonic shallow nucleus-nucleus potential for heavy-ion elastic scattering2. Issue 1 (January 2021) - Sujan Islam, M; Majumder, R; Hossain, S; Nilima, Athoy; Sayed, M A; Shariful Islam, M; Billah, M M; Azad, M M B; Tariq, A S B; Uddin, M A; Basak, A K
Abstract: 'Goldberg criterion' [Goldberg and Smith, Phys. Rev. Lett. 29 (1972) 500] tells that at sufficiently high energies, where pronounced refractive scattering with nuclear rainbow oscillations are followed by an 'exponential-type falloff' in the angular distribution, discrete ambiguities are eliminated for the deep monotonic potential. The criterion is also confirmed in the work of Bartnitzky et al. [Phys. Lett. B 365 (1996) 23] on the 16 O+ 16 O elastic scattering in the energy range of 250 - 704 MeV. However, their finding 'using model-independent potentials' suggests that heavy-ion elastic scattering data unambiguously favour deep potentials. The Goldberg criterion is examined in our work for non-monotonic shallow potentials using the 16 O+ 16 O elastic scattering at energy region up to 350 MeV.